Insight and Intuition - Two Sides of the Same Coin? - Michael Öllinger (Frontiers Research Topics, 2018)
Insight and intuition might be the most mysterious and fascinating fields of human thinking and problem solving. They are different from standard and analytical problem solving accounts and provide the basis for creative and innovative thinking. Until now they were investigated in separate academic fields with differing tradition. Therefore, this eBook attempts to bridge the gap between both processes and to provide a more integrated perspective. Several experts address the underlying cognitive processes and provide a broad spectrum of new empirical, theoretical, and methodological insights.